(untitled) (ENTHYMEMA, 2022)
This paper reconstructs the constellation of the ‘strangest’ contemporary Italian literature, named ‘new Italian weird’ in the on-line debate that accompanied the publishing phenomenon from 2016 to 2018, and compares it with its counterparts in the States United and in Europe to reflect upon how and why literary systems change over time. A semiotic and polysystemic approach has made it possible to trace the modalities of this recent literary feeling back to the wider condition of contemporaneity, whose exasperated features have been defined also in terms of hypermodernity and which today seems to imply an always growing hybridization between the genres of the novel. An element which characterizes this form of extreme literature is the use of the weird, here understood not as a genre in itself, but as an ‘oblique’ device, employed to open up new perspectives and to go beyond the limited possibilities of meaning of reality.